Sarcomatoid carcinoma a rare variant of squamous cell carcinoma of larynx: a case report - Guleria, Trilok C.; Mohindroo, Shobha; Mohindroo, Narender K.; Azad, Ramesh K. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Sarcomatoid (spindle cell) carcinoma is a rare variant of squamous cell carcinoma (SCC). It compromises of 2–3% of laryngeal cancers. Tumor arises from the oral cavity, tonsil, larynx and pharynx. Majority of these tumors are polypoid or pedunculated and tend to cause obstructive symptoms. These tumors are often detected at an early stage, removed by polypectomy during diagnosis and tend to have a very good prognosis. In this case report, 76 years male who presented with progressive hoarseness of his voice and pain in throat. The patient underwent direct laryngoscopy with excision of the malignant mass and received radiotherapy.